ESL pre-university students’ perceptions of the generic rubric used to assess problem-solution essay – a preliminary study / Nur Hani Laily Ramli, Assoc. Prof. Dr Siti Maftuhah Damio and Dr. Sheikha Majid - Ramli, Nur Hani Laily; Damio, Siti Maftuhah; Majid, Sheikha (Universiti Teknologi MARA, Kedah, 2024)
In writing, assessment is conducted to enable language educators to provide feedback regarding students’ development in their learning. Hence, a scoring rubric is one of the teaching and learning tools that can assist language educators in helping students to develop their writing skills. This preliminary study sought the ESL pre-university students’ perceptions towards generic scoring rubric used to assess their problem solution essays. A total of 23 ESL pre-university students at one of the centers of foundation studies in Selangor, Malaysia were involved in this preliminary study through a given adapted questionnaire used by Gutiérrez (2017) to determine the effectiveness of the generic scoring rubric. Data gathered were analyzed using SPSS software version 29 to determine the mean, frequency, and percentage through descriptive statistics analysis. The findings depicted that the majority of the respondents believed that the generic scoring rubric is useful in terms of guiding them to write essays in general. However, the findings also revealed that the rubric is somehow unable to improve their skills in writing problem-solution essays since the descriptions of the rubric’s elements are too general. Thus, the findings suggested that improvement towards the generic scoring rubric is vital to help the ESL pre-university learners’ development in writing problem solution essays as well as for students to understand how their writing is being assessed.